A Case of Histiocytoid Variant Eccrine Sweat Gland Carcinoma of the Orbit - Kim, Young Min (The Korean Ophthalmological Society, 2011)
A 79-year-old male presented with left ocular pain. Evisceration and silicone ball implantation were performed after a diagnosis of phthisis. He returned six weeks later because of left facial erythematous swelling, tenderness, mild fever, chills and cough. His condition was diagnosed as orbital cellulitis. Despite two weeks of empirical antibiotic therapy, the symptoms worsened. A subsequent orbital computed tomography scan revealed enhanced soft tissue infiltrations in his left orbit and eyelid. Biopsy showed a diffusely infiltrating tumor of signet ring cell cytology. A systemic evaluation revealed multiple bone metastases. Based on this evidence, the patient was diagnosed with a very rare case of histiocytoid variant eccrine sweat gland carcinoma with multiple bone metastases.